Pengelolaan Limbah Rumah Tangga Ramah Lingkungan pada Masyarakat Jl. Sosro Gg. Pertama, Kelurahan Bandar Selamat - Indriyani Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Household waste management is an important issue in maintaining environmental quality in densely populated areas. This study was conducted in Bandar Selamat, Jl. Sosro Gg. Pertama, with the aim of increasing public awareness of environmentally friendly waste management practices. A descriptive qualitative approach was used, involving socialization, discussion, and waste sorting practices. The results indicated that the community responded positively, as evidenced by their active participation in the socialization efforts and their interest in utilizing organic waste for composting. However, challenges were identified, including low environmental literacy and the perception that waste management is solely the responsibility of the government. Despite these challenges, the activity succeeded in fostering a collective understanding and raising awareness about the importance of environmentally friendly household waste management. In conclusion, this initiative was successful in engaging the community, and the sustainability of the activity through continued community support is crucial for ensuring the creation of a clean and sustainable environment.